(3agQS eDdaGJ eMji GdOjf Hf YQHis - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf GHf YQHj,J (B638 (3g` s
(3ChdgG (B:s
(3HSe Gddg G dQMef GdQMje CeG HYO aEfg SCdfi HYV GdENhGf Cf CHPdg ai gPg GdChQGb LejY eG UfaJg hCfTCJg ai WQjb GdMbGFb hGdCSQGQ Ydi WQjb GdJUha hai ZjQ gPG Gdaf s
(3BNQgG (B:s
(3hcJGH GdMb hGdHGWd hcJGH Gdedc hGdedchJ hcJGH GdMO heaGJjM GdcfhR GfJgi s
(3HgG fXGe GdJYbjHIs
(3gfGc YdGeI MeQGA YfO cd cdeI cJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B281 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B114s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3agGQS hecJHGJs